Thalictrum argyi (Ranunculaceae) is conspecific with T. fortunei, not T. javanicum - Yuan, Qiong; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
Thalictrum argyi (Ranunculaceae) had been previously placed in synonymy with T. javanicum. We demonstrate that T. argyi is actually conspecific with T. fortunei. We therefore reduce T. argyi, a later name, to the synonymy of T. fortunei. Lectotypification is proposed for T. fortunei.